Ethnographies of Islam: Ritual Performances and Everyday Practices - Baudouin Dupret, Thomas Pierret, Paulo G. Pinto, and Kathryn Spellman-Poots (Edinburgh University Press, 2012)
In the past three decades, the social sciences in general, and anthropology in particular, have developed an ambiguous relationship with their descriptive traditions, as epistemic relativism and self-defeating critique have led scholars to reflexive deadlocks and fruitless glossing over issues. Instead of attempting to describe the social world as it unfolds when empirically observed, researchers often lose the actual object of interest and propose new narratives in its place that are devoid of the contextual and praxiological specificities of any actual situation. This holds especially true where religious phenomena are concerned. This is probably due to a theorising attitude, what Wittgenstein called the â€œcraving for generalityâ€, that looks for big explicative schemes and neglects the situational and self-producing capacity of the social world to produce its own endogenous order. Without advocating a return to positivism, we contend that the social sciences should pay closer attention to actual social practices and adopt a more empirical and analytical attitude vis-Ã -vis their object of scrutiny. We can identify at least three problems in the social sciences which justify some sort of ethnographic re-specification of our attitude vis-Ã -vis â€œthe realâ€. The first one is the tendency to seek for the nature of things instead of their workings, which often results in a â€œdescriptive gapâ€. The second is the quest for data which is often oblivious to the conditions of how this data is produced and thus provide the reader with sketches that somehow miss the phenomena under scrutiny. The third problem resides in the depreciation of descriptive work due to its limited capacity for explanation; although an adequate description is nothing less than a thorough analysis of a chunk of the world as it actually functions. An important development in the social sciences over the past three decades has been the spread of the ethnographic approach beyond the boundaries of anthropology. Nowadays it is fairly common to have researchers in other academic disciplines such as sociology and political science, who use ethnography. This trend has allowed the social sciences to gradually shift their focus from the structural organisation of social systems to the role of people in producing and reproducing social processes through their everyday practices. Let us first define precisely what we mean by â€œethnographyâ€. Recently, it has become increasingly common to call any anthropological research that is based on fieldwork â€œethnographyâ€. In this volume, we adopt a different approach by defining ethnography as the description and analysis of practices from the perspective of the social context in which they were produced. From this point of view, formal interviews are not ethnographic instruments if they are used to collect ex post accounts of practices that were performed in another context; their ethnographic relevance is limited to the moment of the interview itself.